Effect of the deuterium on efficiency and type of adipogenic differentiation of human adipose-derived stem cells in vitro - Zlatska, Alona V.; Vasyliev, Roman G.; Gordiienko, Inna M.; Rodnichenko, Anzhela E.; Morozova, Maria A.; Vulf, Maria A.; Zubov, Dmytro O.; Novikova, Svitlana N.; Litvinova, Larisa S.; Grebennikova, Tatiana V.; Zlatskiy, Igor A.; Syroeshkin, Anton V. (Scientific reports, 2020)
In this study, we performed an adipogenic differentiation of human adipose-derived stem cells (ADSCs) in vitro with different deuterium content (natural, low and high) in the culture medium during differentiation process with parallel analysis of the gene expression, metabolic activity and cell viability/toxicity. After ADSCs differentiation into adipocytes we have done the analysis of differentiation process efficiency and determined a type of resulting adipocytes (by morphology, gene expression, UCP1 protein detection and adipokine production analysis). We have found that high (5 × 10 5 ppm) deuterium content significantly inhibit in vitro adipogenic differentiation of human ADSCs compared to the groups with natural (150 ppm) and low (30 ppm) deuterium content. Importantly, protocol of differentiation used in our study leads to white adipocytes development in groups with natural (control) and high deuterium content, whereas deuterium-depleted differentiation medium leads to brown-like (beige) adipocytes formation. We have also remarked the direct impact of deuterium on the cellular survival and metabolic activity. Interesting, in deuterium depleted-medium, the cells had normal survival rate and high metabolic activity, whereas the inhibitory effect of deuterated medium on ADSCs differentiation at least was partly associated with deuterium cytotoxicity and inhibitory effect on metabolic activity. The inhibitory effect of deuterium on metabolic activity and the subsequent decrease in the effectiveness of adipogenic differentiation is probably associated with mitochondrial dysfunction. Thus, deuterium could be considered as an element that affects the substance chirality. These findings may be the basis for the development of new approaches in the treatment of obesity, metabolic syndrome and diabetes through the regulation of adipose-derived stem cell differentiation and adipocyte functions.